Whistleblowing Intention: The Impact of Commitment and Ethics - Aryani, Novia; Novita, Novita (Association of Certified Fraud Examiners Indonesia Chapter, 2025)
As profit-making businesses, banks have goals for achieving profits to draw in investors and compete with rivals. Setting high goals compels all workers to put in more effort than is necessary, which might lead to fraud as a justification for target completion. It is believed that the degree of bank fraud can be decreased by putting in place a whistleblower mechanism and practicing excellent corporate governance. The factors that can influence employee intentions to whistleblow include professional commitment, organizational commitment and ethical behavior. Financial services firms are anticipated to gain knowledge from this study about the variables that may affect employees’ intentions to be whistleblowers. 110 employees of Bank XX participated in this study as respondents. The parameters for the research sample were established using judgment sampling and purposive sampling procedures. Since the primary data was gathered through the online distribution of surveys using the Google Form link, the study data type falls within the quantitative data category. To gauge respondent’s opinions and assessments, a Likert scale with the following options must be used: (1) strongly disagree to (4) strongly agree. The descriptive method and the verification method using the SEM-PLS approach are the analysis techniques employed. According to the study’s findings, ethical behavior and organizational commitment were found to be able to raise Bank XX workers’ intentions to engage in whistleblowing; professional commitment, on the other hand, had no discernible impact on these intentions. Therefore, it can be said that despite their professional dedication, Bank XX workers are not interested in implementing whistleblowing procedures. This is because they value their loyalty and are afraid of losing their employment, which is their primary source of income